Enhancing the thermal performance of courtyard office building in hot-humid climate : a case study of development department building UniMAP / Esra'a Shehadeh Hussein Abbaas - Abbaas, Esra'a Shehadeh Hussein (School of Environmental Engineering, Universiti Malaysia Perlis, 2018)
This study aims to investigate the effect of the courtyard within the Development Department building at University Malaysia Perlis in Pauh Putra campus and to improve its conditions on the thermal performance and thermal comfort for the building. In this research, the thermal performance is studied based on the indoor air temperature and relative humidity within the building. However, the thermal comfort is evaluated based on the predict mean value (PMV) according to Fanger's model. The objectives of this research can be summarized as follow ; to evaluate the impact of a central courtyard on creating temperature gradient between the outer side and inner side of a building in hot-humid climate ; to investigate the impact of the natural ventilation of the courtyard on the thermal performance and thermal comfort of the building ; to study the window venetian blind shading effect on the thermal performance and thermal comfort of the building ; to explore the glazing effect for the windows on the thermal performance and thermal comfort of the building.